Pengaruh Kompetensi Guru dan Motivasi Belajar Terhadap Prestasi Belajar Siswa OTKP SMKN 1 Boyolangu - Endang Purnawati (Universitas Negeri Surabaya, 2022)
This study aims to determine the influence of teacher competence and learning motivation on student learning achievement. The population in this study were students of classes X and XI majoring in OTKP SMKN 1 Boyolangu with a sample of 165 respondents using a simple random sampling technique. The method of data collection uses questionnaires. The data analysis technique used is a classical assumption test consisting of a normality test, a multicollinearity test, a heteroskedasticity test, a multiple linear regression test, and a coefficient of determination (R2). Furthermore, the last one is a hypothesis test consisting of the T-test and the F test. Results obtained in this study are that there is a significant and positive influence between teacher competence on student learning achievement, learning motivation has a positive and significant effect on student learning achievement, and teacher competence and learning motivation have a simultaneous and positive impact on student learning achievement.